Atlas of head/neck and spine normal imaging variants. (2018) - McKinney, Alexander; Cayci, Zuzan; Gencturk, Mehmet; Nascene, David; Rischall, Matt; Rykken, Jeffrey; Ott, Frederick
No abstract available